Psychosocial implications of curriculum change on Lesotho primary school teachers - Kojana, Retselisitsoe Kitima (University of the Free State, 2019)
The aim of curriculum change is to improve educational programs and practices which could assist to achieve overall educational objectives in a more effective way. Educational change does not happen in isolation, it affects ones ‟cognitive welfare, emotions, norms and habits". The scarcity of literature on psychological and social implications and wellbeing of teachers especially during curriculum change transition and implementation has triggered the researcher to explore psychosocial implications of curriculum change on teachers. The aim of this study is to determine psychosocial implications of curriculum change on Lesotho primary school teachers. The study adopted the qualitative research approach, guided by appreciative inquiry theory and located within the parameters of the interpretivist paradigm. Semi-structured interviews and focus group discussions were deployed for crystalization purposes and to generate data from four sets of participants being primary school teachers, primary school principals, curriculum designers, and subjects assessment packages designers. To ensure trustworthiness and quality five qualitative research design criterions were embraced. Thematic analysis was engaged to analyse data. Findings of this study revealed four broad themes namely, a need for curriculum change; teachers participation in curriculum change; effects of curriculum change; and teachers coping mechanisms. Within these themes there emerged different subthemes which allowed the researcher to analyse and interpret data easily. Study findings also revealed how teachers emotions, attitude, motivation and teachers relationship and social life were affected. Factors like learners continuous assessment, increased workload, lack of teaching aids and learning resources, and unprofessional approach of District Resource Teachers (DRTs) has impacted negatively on teachers motivation. Findings also revealed that different factors were embedded in the social life of teachers during curriculum change and implementation phase. More so, the study also determined psychosocial coping mechanisms which teachers adopted to survive and manage challenges posed by educational changes. The study recommends that curriculum policy makers must not ignore teachers psychological wellbeing when designing and developing curriculum policies. As curriculum implementers, teachers must be allowed to participate in the process of curriculum design. Also, teachers must appreciate and embrace curriculum changes to allow innovation and creativity in schools.
Keywords: Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 2019; Curriculum change -- Lesotho; Curriculum change -- Social aspects; Curriculum change -- Psychological implications; Teachers; Coping mechanisms